A new European species of Nevrorthus in the Iberian Peninsula(Insecta, Neuropterida) - Monserrat, V. J.; Gavira, O. (Zootaxa, 2014)
A new species of Nevrorthus (Insecta, Neuropterida: Nevrorthidae) has been found in the south of the Iberian Peninsula (Spain, Malaga): N. reconditus Monserrat & Gavira n. sp. This new species represents the first record of this genus and this family in the Westernmost Mediterranean basin. A key to the known species of this genus is provided.